2015
DOI: 10.1016/j.ympev.2015.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of frogs from the genus Physalaemus (Anura, Leptodactylidae) inferred from mitochondrial and nuclear gene sequences

Abstract: Although some species groups have been recognized in the leiuperine genus Physalaemus, no phylogenetic analysis has previously been performed. Here, we provide a phylogenetic study based on mitochondrial and nuclear DNA sequences from 41 of the 46 species of Physalaemus. We employed the parsimony criterion using the software TNT and POY and the Bayesian criterion using the software MrBayes. Two major clades were recovered inside the monophyletic Physalaemus: (i) the highly supported Physalaemus signifer Clade,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
130
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(142 citation statements)
references
References 70 publications
9
130
1
2
Order By: Relevance
“…Similar integrative taxonomic approach was carried out by Lourenço et al (2015) for amphibians and Mezzasalma et al (2015) for reptiles. As already pointed out by Cardozo et al (2011) and subsequently confirmed in other works, the species of Ololygon (the former Scinax catharinae clade) have NORs in chromosome pair 6, whereas the species of Scinax (the former Scinax ruber clade) generally have this marker in the chromosome pair 11, which also indicates the conservation of this character to cytogenetically differentiate species of both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Similar integrative taxonomic approach was carried out by Lourenço et al (2015) for amphibians and Mezzasalma et al (2015) for reptiles. As already pointed out by Cardozo et al (2011) and subsequently confirmed in other works, the species of Ololygon (the former Scinax catharinae clade) have NORs in chromosome pair 6, whereas the species of Scinax (the former Scinax ruber clade) generally have this marker in the chromosome pair 11, which also indicates the conservation of this character to cytogenetically differentiate species of both groups.…”
Section: Discussionmentioning
confidence: 99%
“…The Physalaemus cuvieri group is the largest of the Physalaemus cuvieri clade, formed by nine described species, Physalaemus cuvieri Fitzinger, 1826, Physalaemus albonotatus (Steindachner, 1864), Physalaemus centralis Bokermann, 1962, Physalaemus cuqui Lobo, 1993, Physalaemus ephippifer (Steindachner, 1864), Physalaemus erikae Cruz & Pimenta, 2004, Physalaemus fischeri Boulenger, 1890, Physalaemus kroyeri (Reinhardt & Lütken, 1862) and Physalaemus albifrons (Spix, 1824). In the analysis of Nascimento et al (2005), Physalaemus cicada was included in the Physalaemus cuvieri group, although the phylogenetic analyses of Lourenço et al (2015) did not confirm this asssignment.…”
Section: Introductionmentioning
confidence: 96%
“…However, an alternative approach to the phylogeny of these species, based on the analysis of mitochondrial and nuclear data, produced a new proposal, formed by two major clades, Physalaemus signifer and Physalaemus cuvieri . The Physalaemus cuvieri clade encompasses the Physalaemus cuvieri , Physalaemus biligonigerus , Physalaemus henselii , Physalaemus gracilis and Physalaemus olfersii species groups, as well as the species Physalaemus aguirrei Bokermann, 1966 and Physalaemus cicada Bokermann, 1966, whose interspecific relationships remain unclear (Lourenço et al 2015). The Physalaemus cuvieri group is the largest of the Physalaemus cuvieri clade, formed by nine described species, Physalaemus cuvieri Fitzinger, 1826, Physalaemus albonotatus (Steindachner, 1864), Physalaemus centralis Bokermann, 1962, Physalaemus cuqui Lobo, 1993, Physalaemus ephippifer (Steindachner, 1864), Physalaemus erikae Cruz & Pimenta, 2004, Physalaemus fischeri Boulenger, 1890, Physalaemus kroyeri (Reinhardt & Lütken, 1862) and Physalaemus albifrons (Spix, 1824).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations